Haematological changes in HIV infection with correlation to CD4 cell count - Parinitha, SS (Australasian Medical Journal, 2012)
BACKGROUND: HIV infection is associated with a wide range of haematological abnormalities. METHODS AND OBJECTIVES: The objectives in this study were to study haematological changes in HIV patients and to correlate them with CD4 cell counts. Two hundred and fifty HIV positive patients referred to the haematology laboratory section for complete haemogram in whom CD4 count was done were included in the study. Haematologic parameters and CD4 counts were studied in each of these patients. Descriptive statistics were applied. Association between two attributes was calculated by chi-square test and p value less than 0.05 was considered statistically significant. RESULTS: Among 250 patients, anaemia was seen in 210 (84%) cases. The most common type was normocytic normochromic (40.4%). Lymphopenia was seen in 163 (65.2%) cases and thrombocytopenia in 45 (18%) cases. The majority of cases (70%) had CD4 cell counts below 200 cells/mm(3). Fifty-four cases (21.6%) had CD4 counts between 200 to 499 cells/mm(3) and 21 (8.4%) cases had CD4 counts more than 500 cells/ mm(3.) In patients with CD4 counts less than 200 cells/mm(3), anaemia was seen in 91.4% cases, leucopenia in 26.8% cases, lymphopenia in 80% cases and thrombocytopenia in 21.7% cases. CONCLUSION: Haematologic manifestations of HIV infection are common and more frequent with progression of disease. The present study revealed a significant increase in the number of cases of anaemia, and lymphopenia, with decreasing CD4 cell counts. Thrombocytopenia is also seen but does not show significant increase with disease progression. The study also highlights the importance of simultaneously treating HIV patients for haematologic manifestations to reduce morbidity.